﻿Inhibition of the phytopathogenic fungi Curvularia lunata BM and Ganoderma sp. TB4 by antifungal compounds produced by Bacillus siamensis LDR grown on hanjeli (Coix lacryma-jobi L.) starch - Iman Santoso; Qonita Gina Fadhilah; Syella Dwi Safitri; Sri Handayani; Andi Eko Maryanto; Yasman Yasman (Pensoft Publishers, 2022)
Bacillus siamensis LDR was tested for its potential as a biocontrol agent against the phytopathogenic fungi Curvularia lunata BM and Ganoderma sp. TB4. Fermentation of B. siamensis LDR for the production of antifungal compound was performed in modified Czapex-Dox broth using hanjeli (Coix lacryma-jobi L.) starch as carbon source. The Bacillus siamensis LDR inoculum was 105 CFU/ mL, and fermentation was conducted for up to 16 days. Antibiosis assay conducted to test the antifungal activity of filtrate medium. The results showed inhibition of C. lunata BM and Ganoderma sp. TB4 were 47.08% and 85.99%, respectively on 14th day of fermentation. Antifungal assay of the crude extract from filtrate medium revealed growth inhibition of C. lunata BM (60.70%) and Ganoderma sp. TB4 (65.25%). Thin layer chromatography of the crude extract revealed pink-colored spots indicative of lipopeptide compounds. Analysis of the crude extract by ultraperformance liquid chromatography-mass spectrometry was tentatively identified as iturin A, bacillomycin F, and surfactin.